Reliability Engineering Basic Concepts and Applications in ICT - Lazzaroni, Massimo; Cristaldi, Loredana; Peretto, Lorenzo; Rinaldi, Paola; Catelani, Marcantonio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
It is well known that reliability and dependability are assuminga strategic role in all contexts where productperformance and safety are specific requirements. To this purpose this book representsa practical guide for designers and users in Information and Communication Technology area and for those that treat the different stages of the life cycle of products. Starting from the definition of the fundamental terms according to the international standards, basic techniques for the evaluation of the reliability of components and systems are presented. A specific feature of this book is to describe reliability concepts starting from an experimental point of view: for this reason particular attention has beenpaid to laboratory tests. For instance in ICT area, a practical way for evaluating the failure rate for a given system is to use properreliability prediction handbooks. In the book manyexamples are reported to this purpose. Last, the more complex aspects regarding the Dependability of complex systems are taken into account; in particular, some fundamental techniques such as FMECA (Failure Mode, Effects, and Criticality Analysis) and FTA (Fault Tree Analysis) are presented with examples for reparable systems.
Introduction -- The Concept of "Statistical" Reliability -- Reliability Analysis in the Design Phase -- Experimental Reliability and Laboratory Tests -- Reliability Prediction Handbooks: Evaluation of the System Failure Rate -- Repairable Systems and Availability -- Techniques and Methods to Support Dependability -- Qualitative Techniques.
Keywords: Engineering; System safety; Telecommunication; Economics; Business planning; Engineering; Quality Control, Reliability, Safety and Risk; Organization/Planning.; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Communications Engineering, Networks; R & D/Technology Policy